THE DYNAMICS OF EXCHANGE RATES, INFLATION, AND TRADE BALANCE IN A SMALL OPEN ECONOMY (CASE STUDY OF SIERRA LEONE) - Ishmael Kamara; Diah Widyawati (Transpublika Publisher, 2024)
Sierra Leone experiences a persistent trade deficit problem. Currently, there is a vacuum in the literature employing recent data and suitable approaches to address the issue of non-stationarity and dynamic interaction between macroeconomic variables in influencing the trade deficit in Sierra Leone. This study examines the relationship between Sierra Leone's trade balance, inflation, and exchange rate using quarterly data from 2005 Q1 to 2023 Q3. The focus is on understanding how the exchange rate and inflation impact Sierra Leone's trade balance in both the short and long term. To achieve this, the study utilizes the VAR/VECM model to depict the dynamic interaction between the trade balance, exchange rate, and inflation. It also employs Granger Causality analysis to determine the most appropriate ordering among the macroeconomic variables in the model and Impulse Response Function (IRF) analysis to test the hypotheses regarding the trade balance response to exchange rate shocks and inflation. The empirical results confirm the existence of cointegration, indicating a long-term balance between the trade balance, exchange rate, inflation, and other macroeconomic variables such as GDP growth and interest rate differentials. Moreover, the dynamic prediction analysis using the IRF method supports the J-curve hypothesis in Sierra Leone and suggests that inflation can reduce the performance of the trade balance. These findings highlight the need for Sierra Leone to implement a comprehensive strategy to adjust the exchange rate and curb inflation to improve the trade balance and enhance external economic stability.